IMPACT OF COMPANY FINANCIAL RATIO ON SHARE PRICE WITHIN THE PROPERTY AND REAL ESTATE INDUSTRY - Boentoro, Sinta; Adiwidjaja, Sheila (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
Movements in share prices are caused by several factors, both internal and external. The objective of this research is to observe the impact of company financial ratio on share prices within the property and real estate industry using GARCH model. The reason why we chose this industry is because this industry can still grow even when the economic condition is unstable. The research shows that current ratio, debt equity ratio inventory turnover, price earnings ratio and return on equality are jointly significant in predicting share prices. Partially, only price earnings ratio does not significantly impact the share price.